The Effect of Puzzle Cognitive Therapy on the Ability of the Elderly in Hulubalang Village, Paleleh District, Central Sulawesi Province - Arditawanti Hulalu; Inne Ariane Gobel; Andi Nur Aina Sudirman (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
As we age, the human body will undergo physiological and psychological changes. There are setbacks and psychological changes that affect the cognitive abilities of the elderly, thus affecting the inability or difficulty to carry out daily living activities related to the independence of the elderly or activity daily living (ADL). Research Objectives: The purpose of this study is to determine the effect of Cognitive Puzzle Therapy on the ability of the level of independence of the elderly in Hulubalang Village, Paleleh District. The research design used quantitative pre-experiment with a pre-post test design, involving a total of 31 respondents using purposive sampling. Research Results: The results of the study using the non-parametric statistical test Wilcoxon signed rank test showed that there was an Effect of Puzzle Cognitive Therapy on the Ability of the Independence Level of the Elderly in Hulubalang Village, Paleleh District, as evidenced by p. value (0.000 < 0.05). Conclusion: Cognitive Puzzle Therapy has a significant effect on improving the independence ability of the elderly in Hulubalang Village, Paleleh District so that it can be used as an exercise to improve the ability of the elderly to carry out daily activities independently.